Rapid Response of Advanced Squamous Non-Small Cell Lung Cancer with Thrombocytopenia after First-Line Treatment with Pembrolizumab Plus Autologous Cytokine-Induced Killer Cells - Hui, Zhenzhen; Zhang, Xinwei; Ren, Baozhu; Li, Runmei; Ren, Xiubao (Frontiers in Immunology, 2015)
We present the first clinical evidence of advanced squamous non-small cell lung cancer with severe thrombocytopenia showing dramatic improvement after first-line treatment with pembrolizumab plus cytokine-induced killer cells.